Rapid "self-healing" behavior induced by chloride anions to renew the Fe–Ni(oxy)hydroxide surface for long-term alkaline seawater electrolysis. Issue 16 (6th July 2022) - Fan, Ruo-Yao; Zhang, Xin-Yu; Yu, Ning; Wang, Feng-Ge; Zhao, Hui-Ying; Liu, Xin; Lv, Qian-Xi; Liu, Da-Peng; Chai, Yong-Ming; Dong, Bin
Abstract : Due to the surface adsorption and interlayer insertion behavior of chloride anions, the Fe–Ni(oxy)hydroxide catalytic surface is easily destroyed, making it difficult to be used for long-term seawater electrolysis. Abstract : Due to the surface adsorption and interlayer insertion behavior of chloride anions, the Fe–Ni(oxy)hydroxide catalytic surface is easily destroyed, making it difficult to be used for long-term seawater electrolysis. Here, we developed a time- and labor-saving rapid surface reconstruction assisted by a directional anodic corrosion strategy to in situ construct a chrysanthemum shaped active catalytic layer of Fe–Ni(oxy)hydroxide used for seawater electrolysis on the surface of commercial self-supported metal materials. The purpose of the initial artificial anodic corrosion process is to directionally control the rapid corrosion of Fe on the surface of Fe–Ni foam to form a relatively stable Ni-rich structure, which can act as the host of Fe* (Fe* or Ni* represent surface active species of high-valence generated by the oxidation activation) redeposition to slow down the loss of active Fe*. Due to the special structure of the Fe–Ni(oxy)hydroxide catalytic layer tightly loaded on the surface of the Fe–Ni alloy, during the later stability test in natural seawater, the Cl − corrosion can accelerate the surface reconstruction of Fe–Ni(oxy)hydroxide to cause "rapid self-healing", which is not only conducive to the regular renewal of the catalytic layer, but can prolong the stability of its resistance to seawater electrolysis. Eventually, the sample prepared by anodic corrosion and electrochemical reconstruction (named AC-FeNi(O)OH) only required 252 mV of low overpotential to provide a current density of 100 mA cm −2, and also tolerated over 100 hours in alkaline brine and natural seawater.